ANALISIS TINGKAT KUALITAS PELAYANAN JASA MENGGUNAKAN METODE SERVICE QUALITY (SERVQUAL) FUZZY DI INSTALASI RADIOLOGI RUMAH SAKIT UMUM DAERAH (RSUD) PANEMBAHAN SENOPATI BANTUL TAHUN 2012 - Suharyanta, Dwi (Universitas Ahmad Dahlan, 2013)
Background: To provide a quality service to the customer (patient) needs to be a measure of the quality of existing services, covering five dimensions, namely reliability, responsiveness, assurance, empathy, and tangibles in order to create a patient satisfaction. To determine the level of quality, can be measured from the expectations and perceptions of customers (patients). Method: Using the Service Quality (Servqual) method integrated in the Fuzzy. Fuzzy Servqual method is the instrument to measure the service quality between costumers (as patient) expectation and costumers (as patient) perception. Fuzzy set theory to accomode subjectivity and ambiguity on quality service judgement. Conclusion: Using the method acquired Fuzzy Sevqual five attributes / criteria that are a priority for improved quality of services because it has a value of Servqual (Gap) weighted the most. Attributes that are Facilities provided incomplete and inadequate with a value of -1.417 servqual, for the second order The equipment used not using the latest technology (advanced) of -1.313, which is third on The officer has not been attentive to treat patients with a value of -1.250 servqual, for the fourth and final fifth Handling of complaints and Non-radiology is not convenient of -1.146. Where three of the above criteria is of dimension Tangibles, so the main priority to be repaired and improved quality of care is of the dimension Tangibles with a total score of -1.161.The quality of service in the Installation of Radiology of the overall gap calculation results show a negative gap value is -0.961, meaning what is expected according to what the customer has not obtained the customer at the Hospital Radiology Installation Panembahan Senopati Bantul. Keywords: Installing Panembahan Senopati Bantul District Hospital Radiology, Fuzzy, Servqual Gap, Fuzzy-Servqual, Quality service.